EFFICIENCY OF MARKETING OF SOME FRUIT’S CROPS IN THE PROVINCE OF BAGHDAD FOR THE AGRICULTURAL SEASON 2015 / 2014 - & Thamir, Jassim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The high marketing margins for fruit crops and lower marketing efficiency in the province of Baghdad was the target of the study and appreciation it and estimate the relative importance for its as well as marketing costs and measuring Marketing Efficiency for fruit crops studied in the province of Baghdad during the study period 2014/2015.The search has dealt with the evolution of economic indicators for the marketing efficiency of the fruit crops studied in the province of Baghdad during the period of the study it was found that the relative importance of absolute margin catalog between the producer price and consumer price represents a high proportion of which consumers pay, as an average for the total fruit crops studied around 48.80% , and the relative importance of earnings retailer of marketing margin came in the first prize, amounting to an average of the total fruit studied crops around 53.30%, and the wholesaler profits occupied the second highest marketing margin, amounting on average to fruit crops studied 24.37% , and the marketing operations of wholesalers and retailers combined occupied the third place in marketing margin between the producer price and consumer price which reached an average of crops studied about 8.36% This means that the marketing operations have an impact on the prices paid by the consumer the transportation costs occupied the fourth place in terms of relative importance where the averaging for that fruit studied about 7.98% , while the damaged quantities costs came in the fifth rank in terms of the relative importance that reaching an average for Fruit crops studied around 600.% , and measurement of marketing efficiency and the factors influencing them in the study area where it was found the performance weakness of marketing system for fruit crops studied along the marketing channels which are passing through it where the average of the marketing efficiency, according to the three laws used in extracted are 64.87% by the scale 1 with the limits of 40.66% according to the scale 2 and with the limits of 48.50% by the scale 3 It is generally low.One of the main conclusions reached high level of share brokers asymptotic almost to the share of producers of consumer dinars because of their ability to bargain without providing marketing services equivalent to the marketing services provided by the product which thus weakening stimulate producers to develop their production and some of their marketing activities.So the study recommends activating the role of the two devices in order to catalog and indicative determined to take their role in providing guidance and advice to farmers in the marketing of agricultural crops in order to raise efficiency of marketing fruit crops.